Carbon doped iron ore using palm kernel shell - Zamani Abd Rashid, Rusila; Purwanto, Hadi; Mohd. Salleh, Hamzah; Ani, Mohd Hanafi; Akiyama, Tomohiro; Yunus, Nurul Azhani (Trans Tech Publications, Switzerland, 2013)
This paper pertains to the reduction process of local low grade iron ore using palm kernel shell (PKS). It is well known that low grade iron ores contain high amount of gangue minerals and combined water. Biomass waste (aka agro-residues) from the palm oil industry is an attractive alternative fuel to replace coal as the source of energy in mineral processing, including for the treatment and processing of low grade iron ores. Both iron ore and PKS were mixed with minute addition of distilled water and then fabricated with average spherical diameter of 10-12mm. The green composite pellets were subjected to reduction test using an electric tube furnace. The rate of reduction increased as temperature increases up to 900 °C. The Fe content in the original ore increased almost 12% when 40 mass% of PKS was used. The reduction of 60:40 mass ratios of iron ore to PKS composite pellet produced almost 11.97 mass% of solid carbon which was dispersed uniformly on the surface of iron oxide. The aim of this work is to study carbon deposition of PKS in iron ore through reduction process. Utilization of carbon deposited in low grade iron ore is an interesting method for iron making process as this solid carbon can act as energy source in the reduction process